Sustainable Development Reporting: Challenges or Opportunities for Auditors? - Lubenchenko О. Е. (Statistics of Ukraine, 2025)
The Directive of the European Parliament and Council from December 14, 2022 No. 2022/2464/EU on corporate sustainability reporting and the adoption of the European Sustainability Reporting Standards (ESRS) require that business entities and audit firms adapt their organizational processes of reporting and verifications to the new requirements. Ukraine demonstrates its propensity to the European choice by joining the strategies on the way towards Sustainable Development Goals. Hence, an important challenge for domestic enterprises is learning the sustainability reporting requirements, and for domestic auditors it is mastering the techniques for assurance engagements on this reporting. The article contains a review and systematization of the requirements of European legal acts on sustainability reporting, with detailing the structure of report in compliance with ESRS 1; a review of the Recommendations of the Committee of European Auditing Oversight Bodies on assurance engagements and main challenges faced by audit firms in implementing European standards for sustainability reporting, as well as opportunities opened by this practice. The definitions of terms “reasonable assurance” and “limited assurance” were examined. The author analyzed the need for adapting the auditing procedures to new requirements. For the limited assurance engagement, the following procedures were outlined: questioning of business entity’s staff, analytical substantive procedures, tests of control measures, assessment of the evidence from external (alternative) sources. Organizational approaches to the limited assurance engagement on sustainability were proposed, the phases in determining the impact materiality were outlined. A structure of the report on limited assurance on sustainability to be made by the auditor / independent practical specialist was developed. The author’s propositions can be used as a framework for ensuring quality of assurance engagements performed on legal grounds or on request of investors or other stakeholders. European innovations in the sustainable development field, while charging audit firms with a heavy responsibility, open up before them new perspectives and new markets, enhance the auditors’ role in ensuring the resilience and transparency of companies, foster new skills and competences in the domain of sustainability audit.